Gravity modelling of the Tyrrhenian-Calabrian-Ionian subduction system - Akimbekova, A.; Carboni, F.; Mancinelli, P.; Barreca, G.; Scarfì, L.; Pauselli, C.; Monaco, C.; Barchi, M. R. (Frontiers in Earth Science, 2023)
This study provides a lithospheric-scale model along the Ionian Subduction zone in Southern Italy, contributing to the seismotectonic investigation of a region which is affected by relevant historical seismicity. The study employs gravity forward modelling to build the geo-structural model along a composite, NW-SE trending transect extending from the Ionian to the Tyrrhenian Sea, including the Aeolian arc and the Calabro-Peloritan onshore. Through a multidisciplinary approach, we propose new interpretations of three 2D deep-seismic reflection profiles across the study area. Such interpretative profiles are used as constraints to model the observed Bouguer gravity anomalies providing upper and lower crust geometries. Whilst a tomographic model provides constraints for the lithospheric and asthenospheric modelling. The entire workflow is constrained by literature data about Moho geometry, deep seismicity and tomographic images that are integrated to determine the subducting slab geometry. The proposed model of the entire subducting system reasonably fits the observed gravity field and is coherent with the first-order geological and geophysical constraints. The modelling results in updated Tyrrhenian and Ionian Moho depth, subducting slab geometry and location, and densities of the main units, providing valuable input about the composition and geometry of the Calabrian arc structures.